Analysis of the impact of adopting international accounting standards in predicting the insolvency of businesses listed on the BM&FBovespa brazilian stock exchange - Stupp, Diego Rafael; Flach, Leonardo; Mattos, Luísa Karam de (RACE - Revista de Administração, Contabilidade e Economia, 2018)
Abstract: The financial statements of Brazilian companies have been transformed with the adoption of international accounting standards, and it was expected that this would offer more reliable information for decision-making. This study aims to analyze the influence of the adoption of international accounting standards in predicting corporate insolvency. The sample comprises 94 Brazilian companies listed on BM&FBovespa, divided into two groups: the first group has companies considered insolvent and the second group has solvent companies. For each insolvent company we selected another enterprise of the same segment, based on the nearest value of the total assets. The collected data comprised the period of 31 December 2004 to 31 December 2013. The explanatory variables include 29 financial indicators and the methodological procedure was the statistical method called Discriminant Analysis. The application of statistical tests on separate samples in periods before and after the adoption of IFRS, led to the conclusion that there was a considerable improvement in predicting insolvency after the adoption of international accounting standards, because the average accuracy increased from 73.5% to 82.1%. Keywords: Insolvency forecast. Financial indicators. International accounting standards. Análise do impacto da adoção das normas internacionais de contabilidade na previsão de insolvência de empresas listadas na BM&FBovespa Resumo: As demonstrações contábeis das empresas brasileiras foram revolucionadas com a adoção das normas internacionais de contabilidade e espera-se que tragam informações mais confiáveis para a tomada de decisão. O objetivo com este trabalho foi analisar a influência da adoção das normas internacionais de contabilidade na previsão de insolvência empresarial. A amostra compreende 94 empresas brasileiras listadas na BM&FBovespa, divididas em dois grupos: um com empresas consideradas insolventes e outro com as empresas solventes. Para cada empresa insolvente foi selecionada outra do mesmo segmento, com o valor do ativo mais próximo. Os dados coletados abrangem o período de 31 de dezembro de 2004 a 31 de dezembro de 2013. As variáveis explicativas compreendem 29 indicadores contábeis e o método aplicado baseia-se no método estatístico de Análise Discriminante. A aplicação de testes estatísticos em amostras separadas em períodos anteriores e posteriores à adoção das IFRS permitiu verificar que houve uma melhoria considerável na previsão de insolvência após a adoção das normas internacionais de contabilidade, pois a média de acerto aumentou de 73,5% para 82,1%. Palavras-chave: Previsão de insolvência. Indicadores contábeis. Normas internacionais de contabilidade.